The Influence of Liquid Smoke on the Chemical Characteristics of Salted Egg (Faculty of Animal Science Universitas Brawijaya, 2017)
Salted egg is easily preserved of egg products. The making process was added liquid smoke. Therefore, the objective was to determine chemical characteristics (yolk index, oil exudation and salt content) of duck egg salted. Completely Randomized Design (CRD) was used throughout the research. They were run triplicate with differences concentration of liquid smoke (control, 1%, and 1.25%). They were differences salting time process (0, 1, 2, 3, and 4 weeks). Yolk index of control sample were no different statically compared to that of salted egg with liquid smoke treatment (p > 0.05). Significant different of yolk index (p < 0.05) increased along with increase of salting time (4 weeks). Significant differences (p < 0.05) were found on oil exudation of control sample compared to that salted egg with presence of liquid smoke. Oil exudation of salted egg yolk increased with increasing salting time (p < 0.05) up to 4 weeks. Significant differences (p < 0.05) were obtained on the salt content of control compared to that salted egg white treatment of liquid smoke. Salt content white increased along with the increase of salting time (p < 0.05).